2018
DOI: 10.5014/ajot.2018.024273
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy in Medicaid Home and Community-Based Services Waivers

Abstract: OBJECTIVE. Medicaid Home and Community-Based Services (HCBS) 1915(c) waivers are the largest provider of long-term services and supports for people with intellectual and developmental disabilities (IDDs). In this study, we explored how HCBS IDD waivers projected providing occupational therapy services in Fiscal Year (FY) 2015. METHOD. Medicaid HCBS IDD waivers across the nation gathered from the Centers for Medicare and Medicaid Services were qualitatively and quantitatively analyzed to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Occupational therapy is a discipline that uses a variety of procedures and evidence-based devices to help people with injuries, illnesses, and disabilities to strengthen fine and gross motor skills to help them function in daily life. Occupational therapists often target skills such as feeding, leisure activities, dressing, and daily living routines (Friedman & VanPuymbrouck, 2018;Umeda et al, 2017). They also can help teach individuals with IDD how to communicate via assistive devices such as tablet devices in conjunction with speech therapists and behavior analysts (Wilkinson, 2011).…”
Section: Related Disciplines For Sustainable Community Health With Fo...mentioning
confidence: 99%
“…Occupational therapy is a discipline that uses a variety of procedures and evidence-based devices to help people with injuries, illnesses, and disabilities to strengthen fine and gross motor skills to help them function in daily life. Occupational therapists often target skills such as feeding, leisure activities, dressing, and daily living routines (Friedman & VanPuymbrouck, 2018;Umeda et al, 2017). They also can help teach individuals with IDD how to communicate via assistive devices such as tablet devices in conjunction with speech therapists and behavior analysts (Wilkinson, 2011).…”
Section: Related Disciplines For Sustainable Community Health With Fo...mentioning
confidence: 99%
“…As a result, adults with ID have transitioned from living and working in institutional settings to community-based settings (Dean et al, 2015). However, provision of community-based services, including occupational therapy, do not meet current demand (Friedman & VanPuymbrouck, 2018). In order to adequately support adults with ID to live and work inclusively in their communities, occupational therapists must advocate to expand their role beyond traditional service delivery in congregate day and residential settings to that of community-based consultant, program developer, and evaluator (Umeda et al, 2017).…”
Section: Client-level Advocacymentioning
confidence: 99%
“…Occupational therapists can support adults with ID to hire (and terminate) their own staff and provide training to manage their self-directed services budgets. Friedman and VanPuymbrouck (2018) found that many Medicaid waivers did not provide occupational therapy services to adults with ID during the 2015 fiscal year, despite expanded coverage under the PPACA. It is imperative that occupational therapists are aware of the language used to describe habilitation services in their states and that they advocate, with their state-level occupational therapy associations, for a more comprehensive and inclusive definition to increase insurance coverage of habilitative occupational therapy services for adults with ID (Brown, 2014).…”
Section: Client-level Advocacymentioning
confidence: 99%
See 1 more Smart Citation